Barbados : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This 2011 Article IV Consultation highlights that the difficult global economic conditions continue to hit Barbados with growth at anemic levels. The current account deficit has widened in recent times owing to higher oil and food prices. Executive Directors commended the authorities for adopting a revised Medium-Term Fiscal Strategy aimed at generating a balanced budget. They emphasized that fiscal consolidation should focus on expenditure reduction, including lowering the wage bill, reducing transfers to public enterprises, and minimizing tax exemptions.